Evaluation of children diagnosed with a lower respiratory tract infection due to Human metapneumovirus - Kıymet, Elif; Devrim, İlker; Çelik, Tanju; Apa, Hurşit; Soylu, Özlem Bekem; Ecevit, Çiğdem Ömür; Genel, Ferah; Sorguç, Yelda; Çağlar, İlknur; Böncüoğlu, Elif; Bayram, Nuri (The Turkish Journal of Pediatrics, 2022)
Background. Human metapneumovirus (hMPV) is one of the leading causes of acute respiratory infections and bronchiolitis in infants. A history of prematurity and chronic diseases such as congenital heart disease or asthma/reactive airway disease (RAD) increases the risk of severe lower respiratory tract infection (LRTI) due to hMPV. In this cross-sectional study, we aimed to analyze the clinical outcome and risk factors for severe disease in children with LRTI due to hMPV. Methods. The current cross-sectional study included children between 28 days and 18 years of age with the diagnosis of hMPV-associated LRTI hospitalizations, over two years from January 2016 to September 2018 in Health Science University Dr. Behçet Uz Child Disease and Pediatric Surgery Training and Research Hospital. hMPV virus was detected by the multiplex polymerase chain test (PCR) (Commercial Multiplex Real-Time PCR: FTD Respiratory 21 plus, Fast Track Diagnostics, Luxembourg) from a nasopharyngeal swab. Patients who had positive results in multiplex PCR tests with other viral agents simultaneously were not included in the study. Data were retrospectively collected from the computerized hospital system. Results. In this cross-sectional study, 62 patients who were hospitalized with the diagnosis of LRTI due to hMPV infection were included. Thirty-five (55.7%) of the patients were male. The median age was one year (2 months-15 years). Fifty-one (82.2%) patients were younger than two years. The median hospital length of stay was found to be 10 days (2-33 days) in patients with an underlying disease and 7,5 days (ranging from 2 to 20 days) in the patients without an underlying disease, this difference was significant (p=0.031). Conclusions. Clinicians should consider hMPV as an important pathogen of LRTI even in healthy children, although we expect a poor course of disease in children with an underlying disease.
Keywords: hospitalized; human metapneumovirus; length of stay; lower respiratory tract infection